Calm, confidence and hope: A grounded theory study of the coachee experience of receiving coaching support from an educational psychology service. - Allan, Cleo (2023)
There is growing professional interest within Educational Psychology regarding the use of coaching psychology to support casework, at system, staff and individual levels (Adams, 2016b). Research suggests positive outcomes from the use of coaching psychology in schools, but it has been noted that these studies rely on frameworks developed outside of the educational context (van Niewerburgh & Lane, 2012). Additionally, few studies have explored the experience of coaching from the perspective of the coachees; during scoping reviews of the literature, the researcher could find none within the UK educational context. The present study aims to examine the psychosocial processes involved in the coaching experience in schools, from the point of view of coachees. The participants in this study accessed coaching psychology based support from an Educational Psychology Service, giving an opportunity to explore practice in context. To meet this aim, a constructivist grounded theory approach (Charmaz, 2014) was taken to generate a model of coachee experience, grounded in the UK education context. Data was gathered through semi-structured interviews, which was analysed using a complex iterative method of abstraction to generate six categories. These categories were explored alongside the extant literature to develop a theoretical model of the psychosocial processes reported by the coachees. The resultant grounded theory illustrates a process of professional identity change and growth in self-efficacy and wellbeing, through interaction with the coach. Insights into the usefulness of this model are discussed, for coaches, coachees and researchers. Limitations of this study are acknowledged, alongside identified areas for future research.